Study of knowledge and willingness regarding eye donation among medical students of a tertiary care teaching hospital of central India - Ahirwar, Rajesh Kumar; Shidhaye, Pallavi R.; Ekka, Indu J.; Saxena, D. M. (International Journal Of Community Medicine And Public Health, 2016)
Background: Corneal diseases constitute a significant cause of visual impairment and blindness in the developing world. Corneal blindness constitutes 1% of total blindness. Corneal ulcers have also been recognised as a major cause of blindness in developing countries. One of the obstacles in eye donation is lack of awareness and a negative attitude among general population. The willingness about eye donation among medical fraternity definitely will affect the attitude among general population. The present study was conducted to assess the knowledge and willingness about eye donation among medical students of a tertiary care teaching hospital of central India. Methods: A cross-sectional study was carried out in the tertiary care teaching hospital in Bhopal during the period of September 2013 to October 2013. A total of 467 students were selected by convenient sampling. Pre-designed and pre-structured questionnaire was used for data collection. Data were entered in MS Excel sheet and analyzed by STATA-11. Results: A total of 467 students, out of which 263 (56%) were males and 204 (44%) female students and 380 (81.4%) were aware about eye donation. The knowledge regarding eye donation was found to be statistically significant with the gender of the participant (p <0.001). 289 (61.9%) students were willing to donate eyes, out of which 161 (56%) were males and 128 (44%) were females (p=0.73). Among the participants, 97(37%) males and 70 (34%) females did not know about any existing eye bank in MP or India. Conclusions: The present study revealed that most of the students were aware regarding eye donation and most of them were willing to donate their eyes. So continuous awareness programmes and camps should be held and should include not only the community population but also for the undergraduate medical students.